Early-childhood teachers' emotion socialization practices: a multi-method study. Issue 10 (27th July 2022) - Ornaghi, Veronica; Conte, Elisabetta; Agliati, Alessia; Gandellini, Sabina
ABSTRACT: We investigated early-childhood teachers' emotion socialization practices via a multi-method study that combined self-report measures and structured observational situations at day care centre. Eighty-nine teachers ( Mage = 38.29 years; SD = 11.06) completed two questionnaires about their emotion socialization style and beliefs about emotions, respectively. A subsample of 40 teachers also participated in two experimental situations designed for observing their responses to children's emotional distress. We developed an innovative coding system for classifying teachers' reactions in terms of focus (problem, emotion, solution, time) and style (coaching, dismissing, and amplifying, a new style we detected). All teachers deployed a variety of emotion socialization practices. Coaching reactions (especially emotion-focused) were the most frequent, followed by dismissing (problem- and emotion-focused responses) and, to a lesser extent, amplifying responses (mainly problem-focused). There were significant associations between the self-report scores and the responses observed in the experimental situations. We discuss the educational implications of these findings.